1998
DOI: 10.1038/1603
|View full text |Cite
|
Sign up to set email alerts
|

A new intrathalamic pathway linking modality-related nuclei in the dorsal thalamus

Abstract: Transmission of sensory information through the dorsal thalamus involves two types of modality-related nuclei, first order and higher order, between which there are thought to be no intrathalamic interactions. We now show that within the somatosensory thalamus, cells in one nucleus, the ventrobasal complex, can influence activity in another nucleus, the medial division of the posterior complex. Stimulation of ventrobasal complex cells evoked inhibitory postsynaptic currents in cells of the medial division of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(92 citation statements)
references
References 51 publications
6
84
0
Order By: Relevance
“…All of these structures are responsive to visual stimulation. In addition, recent studies revealed that supposedly unisensory thalamic nuclei can modulate each other via the thalamic reticular nucleus (Crabtree et al, 1998;Crabtree and Isaac, 2002). It is likely that such subcortical exchange of multisensory information occurs between visual and auditory modalities, yet this hypothesis has not been tested.…”
Section: Pathways Of Multisensory Enhancement Of Auditory Cortexmentioning
confidence: 99%
“…All of these structures are responsive to visual stimulation. In addition, recent studies revealed that supposedly unisensory thalamic nuclei can modulate each other via the thalamic reticular nucleus (Crabtree et al, 1998;Crabtree and Isaac, 2002). It is likely that such subcortical exchange of multisensory information occurs between visual and auditory modalities, yet this hypothesis has not been tested.…”
Section: Pathways Of Multisensory Enhancement Of Auditory Cortexmentioning
confidence: 99%
“…First, in agreement with our experience in rats , the reticulothalamic input to the ventral posterior nucleus is already highly topographic even at this age, suggesting an early development of the somatosensory system in rats and mice. Second, injection of retrograde tracers into the posterior nucleus has indicated that differences between the reticular inputs to the first-and higher-order relays are found in adults (Crabtree 1996;Crabtree et al 1998).…”
Section: Technical Considerationsmentioning
confidence: 99%
“…One difference is suggested by prior retrograde tracing studies in cats and rats: the higher-order posterior nucleus was reported to have a more diffusely organized reticulothalamic input compared with the first-order ventral posterior nucleus (Crabtree 1996;Crabtree et al 1998). Labeling of a large number (Ͼ100) of cells juxtacellularly in the somatosensory and other sections of the thalamic reticular nucleus of rats, however, has led to a somewhat different conclusion, namely, that the axonal arbors of reticular neurons are mostly circumscribed, quite topographically organized and usually contained within a single thalamic nucleus (Pinault and Deschênes 1998;Pinault et al 1995).…”
Section: Introductionmentioning
confidence: 97%
“…Our mapping results do not provide direct information regarding the anatomical basis (axodendritic vs dendrodendritic) of intranuclear inhibition. Topographic and sensory modality-specific organization exist in nRt both longitudinally (sectors), as well as within the mediolateral extent of the nucleus (tiers) (Jones, 1975;Shosaku et al, 1984;Crabtree, 1996;Crabtree et al, 1998;Lam and Sherman, 2005). For example, neurons located in the central tier of somatosensory nRt project to the ventral posterior nuclei, whereas medial tier neurons connect to the posterior complex (Crabtree, 1996).…”
mentioning
confidence: 99%